Hubungan Tingkat Pencapaian Prestasi Olahraga Futsal dengan Prestasi Akademik pada Mahasiswa Studi Pendidikan Jasmani Kesehatan dan Rekreasi Tahun 2020 - Prakoso, Rio Rizki Adi; Nurharsono, Tri (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine and analyze the relationship between the level of achievement of futsal sports with academic achievement in students of education, physical, health, and recreation studies. This research uses correlational research method. The population in this study were students of UKM futsal Unnes. The data analysis technique used the product moment correlation test. The results of the research and discussion show that the correlation coefficient between the level of sports achievement and academic achievement of 0.681 is positive, meaning that the better the value of the level of sports achievement, the better the value of academic achievement. The significance test of the correlation coefficient was carried out by consulting the price of rcount with rtable, at = 5% with N = 34 obtained rtable of 0.329. The correlation coefficient between rx.y = 0.681 > r(0.05)(34) = 0.329, meaning that the correlation coefficient is significant. The conclusion in this study is that there is a significant positive relationship between the level of achievement of futsal sports achievements and the academic achievements of PJKR UNNES students batch 2020. It is hoped that students can use it as study material in improving academic achievement by paying attention to their sports achievements.